Female ownership and female directors’ moderating role as corporate governance monitoring mechanisms in increasing the value of Thai family-owned firms - Wonlop Writthym Buachoom; Yot Amornkitvikai; Omar Al Farooque; Lan Sun (Gender in Management An International Journal, 2023)
Purpose The phenomenon of “broken rungs” has prevented most women from attaining managerial positions relative to men. Despite this gender disparity in management, female executives are more likely to enhance shareholder trust due to higher ethical standards, which can be hypothesized to mitigate the negative impact of family ownership on firm value. Therefore, this study aims to investigate the moderating role of female ownership and female directors in mitigating the unfavorable effects of family ownership on firm value as measured by Tobin’s Q and the Market Value of Equity (MVE). Design/methodology/approach Multiple linear regression is applied to examine the proposed hypotheses, as well as other vital factors, such as board independence (BI), the dual chief executive officer (CEO)–chairman role (CEO duality) and control variables (i.e. firm size, firm age, leverage and investment ratio). Findings The results revealed that female directors could buffer the negative impact caused by family ownership, leading to higher firm value, when given a sufficient level of female ownership or the appointment of more female directors, regardless of female ownership levels. Otherwise, female ownership cannot help overcome the negative effects of family ownership in Thai-listed firms. This study also sheds light on corporate governance elements that impact firm value. CEO duality reduces the value of Thai-listed companies, whereas board independence increases firm value. Practical implications The managerial roles for women should be promoted in Thai-listed enterprises. The government can support new laws, policies and programs for embracing a cross-cutting gender perspective. Female network initiatives enable women to advance in their managerial careers. Originality/value To the best of the authors’ knowledge, this study intends to fill the research gap by investigating how female directors and owners can moderate family ownership’s influence on the value of firms listed on the Stock Exchange of Thailand (SET), which is one of the emerging capital markets.
Keywords: Family Business Performance and Succession; Corporate Finance and Governance; Entrepreneurship Studies and Influences